Programa educativo para a assistência de enfermagem a pacientes ortopédicos em um hospital de ensino - Brandão, Vânia Zaqueu (2008)
This research is based on evaluations on the nursing care to orthopedical patients in a school hospital; highlighting the nurses' education in this aspect. Objective: To identify important aspects of the nursing care provided to orthopedical patients assisted in a school hospital of the interior of São Paulo state, to propose and introduce educational actions for these nurses. Casuistics and Method: Accomplishment of a case study on nursing care to the orthopedical patients, and educational activity for the nurses after the Ethics Research Committee has approved the study. Instruments tested previously such as interviews were used to collect data into two hospital units for orthopedical patient hospitalization. Forty nursing professionals performing in the orthopedical units, 12 nurses, 27 auxiliary nursing and 1 nursing technician participated in the study. Results and Discussion: Most of them were female (91.7% of the nurses and 82.1% of the nursing team); mean age group 36.4 years among the nurses and 35.7 years among the nursing team; the nurses ´mean time of nursing graduation was12.3 years, and 1 to 5 years the nursing team; no nurse had specialization related to the orthopedics, while the nursing team had informal orientation on the care from the doctors and nurses. The actions more reported were: dressing work-up, body hygiene and the medical prescription follow-up. Some difficulties were pointed out: these patients' complexity, deficiencies in the building plan and furniture; deficit in the orientation of the team, the patients and companions; reduced number of staff; delay in setting the surgeries; early handle of the dressings; moreover, problems in the interaction with medical team and to introduce the nursing care systemization. Six educational meetings developed in three moments took place: with talkative expository class, practical living and finalization, being discussed important subjects such as: dressings, motion, body hygiene, medical prescription follow-up, physical examination, interview, orientations for the team, patient and companion, daily visits, discharge orientation, pain control, pre and postoperative period, specific cares with traction and external fixators, the patients' motion. Conclusions: Some deficiencies were pointed out in the nursing care regarding the orthopedical patient in this hospital, introducing several recommendations, such as better nurses´education, training of the team in the area, to introduce a system of the patients' classification to provide proper place for the nursing staff necessary to improve systemization of the nursing care to the orthopedical patient and to motivate further research on the work management process in Orthopedics in this hospital.